2020
DOI: 10.1002/ajb2.1441
|View full text |Cite
|
Sign up to set email alerts
|

Is selfing a reproductive assurance promoting polyploid establishment? Reduced fitness, leaky self‐incompatibility and lower inbreeding depression in neotetraploids

Abstract: Premise Newly formed polyploids face significant obstacles to persistence and population establishment because of fitness costs of intercytotype mating. Selfing provides the opportunity to escape mate limitation, enabling production of new individuals and increasing the likelihood of fixation of new polyploid lineages. Still, association between self‐compatibility and polyploidy is not always clear. We compared self‐incompatibility and inbreeding depression in neotetraploids and their diploid progenitor to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 118 publications
(167 reference statements)
2
21
0
Order By: Relevance
“…Barringer ( 2007 ) also found that polyploids were more self-fertile compared to diploids based on the analysis of 235 flowering plant species. Our results support the hypothesis that there might be a leaky self-incompatibility in neotetraploids caused by polyploidization (Siopa et al, 2020 ). Furthermore, a recent study found that intensive selection for breeding high seed-yielding tetraploid red clover may increase self-pollination (Vleugels et al, 2019b ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Barringer ( 2007 ) also found that polyploids were more self-fertile compared to diploids based on the analysis of 235 flowering plant species. Our results support the hypothesis that there might be a leaky self-incompatibility in neotetraploids caused by polyploidization (Siopa et al, 2020 ). Furthermore, a recent study found that intensive selection for breeding high seed-yielding tetraploid red clover may increase self-pollination (Vleugels et al, 2019b ).…”
Section: Discussionsupporting
confidence: 91%
“…The doubling of chromosome sets may disturb the self-incompatibility, which is controlled by the S-alleles (Taylor and Quesenberry, 1996 ; Amdahl et al, 2016 ; Vleugels et al, 2019a ). In neotetraploids, reduced plant reproductive success has been linked to larger variations in the self-incompatibility expression compared to diploids (Siopa et al, 2020 ). However, for high seed-yielding tetraploid red clover genotypes, a high self-pollination rate of 83% on average was found (Vleugels et al, 2019b ).…”
Section: Introductionmentioning
confidence: 99%
“…sabularia). Nevertheless, even if diploids were capable of dispersing to southern locations, they may not find a suitable site to establish or may experience strong frequency dependent selection within tetraploid populations (Levin, 1975;Husband, 2000), particularly being a self-incompatible plant (Siopa et al, 2020). Occasional migration from the diploid area into the tetraploid range may allow some rates of gene flow (e.g., through triploid bridge) that could attenuate divergence in environmental requirements between cytotypes of var.…”
Section: Current Distribution Patterns At the Zones Of Sympatrymentioning
confidence: 99%
“…Thus, evolution of self-fertility could be a mechanism that counteract the MCE allowing new tetraploids to establish within a diploid population. The collapse of self-incompatibility and the mitigation of inbreeding depression are often caused by polyploidization itself, and contribute to the establishment of polyploid population at initial colonization stage ( Siopa et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are several studies reporting the occurrence of polyploid populations at the marginal parts of the whole distribution area ( Rivero-Guerra 2008 ; Karunarathne et al 2018 ; Kudo and Hirao 2020 ). High ploidy level can contribute to maintain genetic variability and reduce inbreeding depression ( Rosche et al 2016 ; Rosche et al 2017 ; Siopa et al 2020 ), and improve the performance of vegetative properties ( Otto 2007 ), thus polyploidization may facilitate the maintenance of isolated populations and accelerate local adaptation ( Abeli et al 2014 ). Although there are some studies focusing on the ecological characteristics of small and isolated marginal populations (e.g.…”
Section: Introductionmentioning
confidence: 99%